Qualitative and Quantitative Analysis of Vitamin C in Papaya by UV-Vis Spectrophotometry Method - Rini Lestari; Sri Darmayanti (JURNAL PROTEKSI KESEHATAN, 2021)
Vitamin C is an antioxidant compound that can prevent oxidation processes in the body. Vitamin C is naturally found in fruits and vegetables, one of which is papaya. This study aims to identify and determine the levels of vitamin C in papaya arum fruit variants in Bogor, California, and Bangkok. This study uses a descriptive qualitative and quantitative test method with UV-Vis spectrophotometry. The maximum wavelength for comparison of vitamin C is 264.6 nm. The r value obtained is 0.9956 with a linear regression equation Y = 0.0541X + 0.0791. In this study, the maximum wavelength of vitamin C in Bogor arum papaya was 264.4 nm with a concentration of 123.8 mg/100 g, California papaya 263.4 nm with a concentration of 106.6 mg/100 g, Bangkok papaya 261.2 nm. with levels of 85.2 mg/100 g. The three papaya samples contained vitamin C, marked by the maximum wavelength value in the sample being almost the same as the maximum wavelength value for the comparison standard of vitamin C.